68.4k views
1 vote
Add: 3x+9/2x+6+8x+12/x^2+6x+9

User Adirael
by
5.6k points

1 Answer

2 votes

Answer: X = sqrt[4]{\frac{36}{-34} }

Explanation:

First

you are going to plus all the common denominators.

3x + 6x + 8x = 17x

6 + 9 = 15

Second

then we get the following equation

15 + 17x + 9/2x + 12/x^2

Thirst

then you pass the 17x to the other side with subtraction sign

-17x = 15+ 9/2x + 12/x^2

fourth

after that, the values which are dividing pass to the other side multiplying

-17x . 2x . x^2 = 15+ 9 + 12

fifth

If we resolve the equation in both sides we get the next values

-34x^4 = 36

sixth

then pass the -34 to the other side dividing

x^4 = 36/-34

seventh

after that, pass the exponent of the (X) to the other side

X = sqrt[4]{\frac{36}{-34} }

Add: 3x+9/2x+6+8x+12/x^2+6x+9-example-1
User Florieger
by
5.6k points